The Compartmental Tongue. - Wrench, Alan A. (Journal of Speech, Language & Hearing Research)
Purpose: Tongue anatomy and function is widely described as consisting of four extrinsic muscles to control position and four intrinsic muscles to control shape. This myoarchitecture cannot, however, explain independent tongue body and blade movement nor accurately model the subtlety of observed lingual shapes. This study presents the case for a finer neuromuscular structure and functional description. Method: Using the theoretical framework of the partitioning hypothesis, evidence for neuromuscular compartments of each of the lingual muscles was discerned by reviewing studies of lingual anatomy, hypoglossal nerve staining, hypoglossal motoneuron axon tracing, muscle fiber type distribution, and electromyography. Muscle fibers of the visible human female were manually traced to produce a three-dimensional atlas of muscular compartments. A kinematic study was undertaken to determine the degree of independent movement between different parts of the tongue. A simple biomechanical model was used to demonstrate how synergistic groups of compartments can control sectors of the tongue. Results: Results indicated as many as 10 compartments of genioglossus, two each of superior and inferior longitudinal, eight of styloglossus, three of hyoglossus, and six each of transversus and verticalis, while palatoglossus may not have a significant role in tongue function. Kinematic analysis indicated independent control of five sectors of the tongue body, and biomechanical modeling demonstrated how this control may be achieved. Conclusion: Evidence is presented for a lingual structure based on neuromuscular compartments, which work together to position and shape sectors of the tongue and independently control tongue body and blade.